Campania: Territory and City in front of the Challenge of Logistics - Mazzeo, Giuseppe (TeMA - Journal of Land Use, Mobility and Environment, 2011)
Logistics can be defined as the process of planning, organization and control of all the activities of transportand storage of goods and informations; it interests all the productive phases, from the acquisition of rawmaterials, to the production process in the factories, up to the delivery of the finished products to the finalcustomers. In this way the logistics intersects the territory at different stages of its activity: when the rawmaterials are brought to the factory, when the factory sends semi-production units to other factories, whereproducts are stored in equipped areas, and when the final goods are brought to terminal sales.Inside the Southern territorial system the Campania is an important hub in the transport and sorting ofgoods. This role has made stronger after the carrying out of new logistics infrastructures, related to othersupport infrastructures, as railways and motorways.The regional system presents nationwide excellence’s peaks that could encourage its role in this sector, butthere are also negative factors that may to slow the take-off of the sector. The reference is to theinfrastructures and operating bottlenecks interfering its efficiency, but also to the weakness of the regionalproduction’s system that doesn’t ensures a local critical mass to the logistics.A third aspect is the lack of a clear structure of programming investment and of a greater transparency inthe roles assigned to various initiatives, arising mainly on local, uncoordinated pushes.The paper analyzes the situation of logistics and of its spatial interrelationships in Campania, identifyingstrengths, weaknesses, and potential evolutionary factors. The discussion faces up aspects of territoriallogistics: it differs from the urban logistics for the amount of handled commodities and for the concentrationin strategic poles, because these logistics platforms require specialized equipments and wide spaces formovement and deposit.The first part of the paper analyses the relationships between territory and logistics and identifies either themain elements of interconnection or crisis in the use of physical space, due to the diverging objectivesbetween territorial government and economic actors.The second part considers the condition of good’s movement in relation to the Mediterranean port facilities,to the state of the regional logistics system, and to the economic and territorial Campanian situation.To this purpose, the paper also explores the evolution of territorial planning in Campania, highlighting howa series of choices, including those related to the location of logistics facilities, have been made outside ofexisting planning tools.